Intelligent Marine Technology and Systems - Dong, Junyu; SpringerLink (Online service) (Singapore : Springer Nature Singapore : Imprint: Springer.)
Intelligent Marine Technology and Systems (IMTS) is a high-quality international platform for the exchange the latest discoveries from global artificial intelligence in marine technology and systems. IMTS is an Open Access (OA) journal. The journal is intended for marine artificial intelligence and marine big data, marine environment perception (including physical environment perception and biological environment perception). The journal will publish original papers of innovative idea and concepts, new discoveries and improvements as well as novel applications. The areas that the journal cover include, but are not limited to: 1. Marine artificial intelligence and Marine big data: including ocean phenomenon recognition, ocean data super resolution, ocean phenomenon prediction, ocean multimodal data processing, underwater pattern recognition, big data collection and transmission, ocean big data storage and management, ocean big data information mining, ocean big data visualization and analysis, etc. 2. Marine environment perception: (1) Physical environment perception, including underwater acoustics, underwater optics, marine remote sensing, marine internet of things; (2) Biological environment perception: including using all kinds of intelligent technology and systems to understand biological oceanography, interactions between marine organisms, marine ecosystem dynamics, marine biotelemetry, etc. 3. Marine instruments and engineering: including marine exploration equipment, ocean energy utilization, deep-sea operation instruments, underwater robots, and other instruments and application technologies related to marine resources exploitation and marine environment governance, etc. .
Keywords: Oceanography; Freshwater ecology; Marine ecology; Artificial intelligence; Quantitative research; Image processing$1 (BDigital techniques.s; Computer vision; Ocean Sciences; Freshwater and Marine Ecology; Artificial Intelligence; Data Analysis and Big Data; Computer Imaging, Vision, Pattern Recognition and Graphics